The effect of nano-hydroxyapatite and casein phosphopeptide-amorphous calcium phosphate with and without laser irradiation on the microhardness and surface morphology of demineralized primary enamel: An in vitro experimental study - Anil Tanaji Patil; Tanaya Rajeev Kulkarni; B. Sandhyarani; Sujatha Paranna; Renuka Bhurke; Ankita Annu (Wolters Kluwer Medknow Publications, 2024)
Background: Various topical gels, varnishes, and fluoride gels are being used by dentists for the treatment of White spot lesions (WSLs). The remineralizing effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), nano-hydroxyapatite (nHAp), and lasers has been proven earlier. This study was designed to evaluate the remineralizing effect of nHAp and CPP-ACP with and without erbium-doped yttrium aluminum garnet (Er: YAG) laser irradiation on demineralized primary enamel. The aim of this study was to evaluate the effect of CPP-ACP and nHAp with and without Er:YAG laser irradiation on the microhardness and surface morphology of demineralized primary enamel. Materials and Methods: The present study is an experimental in vitro study. Fifty extracted primary incisors were selected for the study. Following cleaning and sectioning, teeth were embedded in acrylic. The tooth models were divided into four groups randomly - Group 1 (CPP-ACP), Group 2 (nHAp), Group 3 (CPP-ACP + laser), and Group 4 (nHAp + laser). The baseline, postdemineralization, and postremineralization Vickers hardness testing was performed. One sample from each group was analyzed by scanning electron microscopy. Descriptive statistics such as frequencies and percentages for categorical data, mean and standard deviation for numerical data were depicted. The normality of numerical data was checked using the Shapiro-Wilk test. The level of significance was kept at 5%. Intergroup comparison (>2 groups) was done using one-way analysis of variance followed by pair-wise comparison using the post hoc test. Results: There was a statistically significant increase in surface microhardness in each group after remineralization. The highest increase in microhardness value was seen in Group 4 (nHAp + laser) followed by Group 3 (CPP-ACP + laser) and the least in Group 1 (CPP-ACP). Similar observations were made in scanning electron microscopic images. This indicated that nHAp has a comparable, if not better ability for remineralization than CPP-ACP. The remineralizing capacity of both the remineralizing agents was seen to be improved in this study when simultaneous laser application was employed. Conclusion: Currently, the evidence supporting the efficacy of nHAp dentifrices and laser in primary teeth is limited. Additional long-term in vivo studies employing standardized protocols and large sample sizes are necessary to draw definitive findings about the effect of remineralizing agents and lasers on primary enamel.